M’addib s and Migrant Laborers: Migration from Ottoman Trablus al-Gharb to Djerba, Tunisia in the Early 20th Century - Love Jr, Paul M. (International Journal of Middle East Studies, 2025)
This article follows the history of migration from the mountain villages of the Jebel Nafusa in Ottoman Trablus al-Gharb (in today’s northwestern Libya) to the southern Tunisian island of Djerba in the early 20th century. It situates this local history of migration within the broader framework of Maghribi migration both before and during the colonial era in Libya (1911–43), while tracing the histories of two categories of migrants, in particular, manual laborers and Qur’an teachers (m’addib-s). The article makes three claims: (1) Nafusi migration was as much the result of local historical circumstances as it was a response to colonialism; (2) the historical experience of migration of Nafusis differed according to social class; and (3) local circumstances shaped the dynamics of migrant integration in the Maghrib. In doing so, I demonstrate how Nafusi migration to Djerba both conforms to and diverges from the larger history of late Ottoman and colonial-era migration in Tunisia. By shifting the focus away from the colonial moment, I make the case for foregrounding longer-term regional connections and migrations that linked different spaces across the Maghrib and also attend to local histories and what they offer in the way of caveats and exceptions.
Keywords: Bumas'ud, mosquée (Ajim, Djerba); Emigration -- Djebel Nefousa -- Djerba; Enseignement -- Djerba -- 1881-1956; Malāq, mosquée (Oualegh, Djerba); Tâjdît, Mosquée (Fâtû, Djerba)

al-Sulṭā tughlaq Jāmaʿ Malāq bi-Wālagh fī intiḍār hasm al-nizāʿ qānūniyyan bayn al-mutanāziʿīn ʿalayha min al-Ibāḍiyyīn wa Salāfiyyīn - Jarīrī, ʿAbd al-Ḥalīm al- (al-Jazira, 2013)
Keywords: Malāq, mosquée (Oualegh, Djerba)